2017
DOI: 10.1002/ece3.3147
|View full text |Cite
|
Sign up to set email alerts
|

Floral scent and species divergence in a pair of sexually deceptive orchids

Abstract: Speciation is typically accompanied by the formation of isolation barriers between lineages. Commonly, reproductive barriers are separated into pre‐ and post‐zygotic mechanisms that can evolve with different speed. In this study, we measured the strength of different reproductive barriers in two closely related, sympatric orchids of the Ophrys insectifera group, namely Ophrys insectifera and Ophrys aymoninii to infer possible mechanisms of speciation. We quantified pre‐ and post‐pollination barriers through ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 76 publications
0
33
0
1
Order By: Relevance
“…McCormick & Jacquemyn, 2014; Jacquemyn et al ., 2015; Rasmussen et al ., 2015). Some phylogenetically close species are known to share mycorrhizal partners in sympatry, suggesting that mycorrhizal symbiosis has not played a role in reproductive isolation (Gervasi et al ., 2017), as in other orchid genera (Schatz et al ., 2010). The generation time from a seed to a reproductive plant is still not known precisely, but, according to observations of seedling development, may take between two and several years (Fabre, 1852; Hutchings, 2010; Jacquemyn & Hutchings, 2015).…”
Section: The Bee Orchids and Their Pollinatorsmentioning
confidence: 90%
See 3 more Smart Citations
“…McCormick & Jacquemyn, 2014; Jacquemyn et al ., 2015; Rasmussen et al ., 2015). Some phylogenetically close species are known to share mycorrhizal partners in sympatry, suggesting that mycorrhizal symbiosis has not played a role in reproductive isolation (Gervasi et al ., 2017), as in other orchid genera (Schatz et al ., 2010). The generation time from a seed to a reproductive plant is still not known precisely, but, according to observations of seedling development, may take between two and several years (Fabre, 1852; Hutchings, 2010; Jacquemyn & Hutchings, 2015).…”
Section: The Bee Orchids and Their Pollinatorsmentioning
confidence: 90%
“…Claessens & Kleynen, 2011), although variable in space and time (Table 1). Three studies report that this crucial fitness parameter depends significantly on Ophrys population spatial structure (Vandewoestijne et al ., 2009; Gervasi et al ., 2017; Borràs & Cursach, 2018). Considering Ophrys species as separately evolving metapopulation lineages has the immense merit of putting the evolutionary dynamics associated with pollination by sexual swindling into a spatio‐temporal context.…”
Section: The Bee Orchids and Their Pollinatorsmentioning
confidence: 99%
See 2 more Smart Citations
“…Floral scents function as olfactory cues for pollinator attraction and play a vital role in reproductive isolation. Studies of sexually deceptive orchids have indicated that the interaction between floral scent and pollinators promotes speciation, e.g., Chiloglottis 46 and Ophrys 3 , 47 , 48 . This phenomenon has also been discovered in other non-deceptive pollination groups, e.g., Silene 49 , Petunia 50 , and Mimulus 51 .…”
Section: Discussionmentioning
confidence: 99%